IMPLEMENTASI SUPERVISI KLINIS DALAM MENINGKATKAN PROFESIONALISME GURU - ASTUTI, ASTUTI (DIDAKTIKA, 2017)
This journal discusses the implementation of clinical supervision in improving teacher professionalism. Clinical Supervision is a guidance process aimed at assisting professional development of teachers / prospective teachers, especially in teaching performance based on observation and analysis of data accurately and objectively as guidance for the change of teaching behavior. This supervision puts pressure on the process of "professional formation and development" with the intention of responding to the main understanding and needs of teachers related to their duties. The formation of professionalism of teachers who intend to support educational reform as well as to "combat" the deterioration of education must primarily begin by teaching teachers in the classroom. With improvements and improvements expected students can learn well so that the goals of education and teaching can be achieved optimally.